Oxoammonium Salt‐Mediated Vicinal Oxyazidation of Alkenes with NaN3: Access to β‐Aminooxy Azides. Issue 22 (14th September 2021) - Chen, Fei; Tang, Yu‐Ting; Li, Xin‐Ru; Duan, Yan‐Yan; Chen, Chao‐Xing; Zheng, Yang
Abstract: An approach to the vicinal oxyazidation of alkenes has been achieved under mild and transition metal‐free conditions. This method utilizes NaN3 as the azidation agent and 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxoammonium tetrafluoroborate (TEMPO + BF4 − ) as the single‐electron oxidant as well as the oxygen source. By using this protocol, various β ‐aminooxy azides were synthesized and several complex bioactive molecules were functionalized. Abstract :